THE EFFECT OF ANTICIPATION GUIDE STRATEGY ON STUDENTS' READING COMPREHENSION OF EXPLANATION TEXT - Asriani Hasibuan; Aprida Irmayana; Nina Nurbaidah; Dewi Damayanti (JURNAL EDUCATION AND DEVELOPMENT, 2024)
The objectives of this research are to know : 1. The application of anticipation guide strategy on students reading comprehension of explanation text, 2. The students reading comprehension of explanation text before and after using anticipation guide strategy , 3. Is there any significant effect of anticipation guide strategy on students reading comprehension of explanation text at the eleventh grade of SMK Negeri 1 Tantom Angkola. This research use experimental method with one group pre-test and post-test design. The population are 175 with 36 sample take by purposive sampling. The instruments of this research are observation sheet and test form multiple choices. The data is analyze by using t test formula. The result of data analyzing ttest is higher than t table (22.64>2.03). The hypothesis is accepted, it means that there is any significant effect of anticipation guide strategy on students reading comprehension of explanation text at the eleventh grade of SMK Negeri 1 Tantom Angkola in 2022/2023 Academic Year.